Economic System of Taq Taq Township: A Field Anthropology Research - Alan salah saadi; Noori yassin harzani (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
Economic system signifies all the organized status, procedures and plans that associates with the process of production, service, distribution, and consumption by the society members within a certain social framework. Economic system is a part of social systems of society within the structure of social foundation. This field is an essential part of social anthropology. Taqtaq sub-district is recognized by a multi-dimensional and a generalized economy due to its geographical location. This study covers all the economic activities that have a great influence the inhabitants’ social life. The study aims at illustrating the social life of Taqtaq society, statin all the economic changes in the structure of society, and revealing the problems in the economic system of the society. This study adopts a qualitative anthropological approach conducted in the center of Taqtaq Sub-district with the use of anthropological field method based on the constructional functional theory. In the process of data collection, this study makes use of many tools including observation, direct participation in the field of research, interview, reporter, formal, records, data and documents. Based on the collected data on the economic system of this town, we can conclude that the majority of the Taqtaq inhabitants prefer to work for governmental sectors, but due to the consequences of economic crises, and the stop of hiring process by government, the majority of its inhabitants work in agriculture, fish farming and trade. Moreover, the existence of Little Zab River in Taqtaq leads to the flourishing of tourism sector in the area. However, the decrease of oil production amount from 148000 to 5000 in Taqtaq’s oil field has changed the economic system and the nature of social relations in the examined field.